A sharp end to sugary Wingless travels - Droujinine, Ilia A. (The Rockefeller University Press, 2014)
Drosophila melanogaster follicle stem cells are controlled by Wingless (Wg) ligands secreted 50 µm away, raising the question of how long-distance Wg spreading occurs. In this issue of JCB, Wang and Page-McCaw (2014. J. Cell Biol. http://dx.doi.org/10.1083/jcb.201403084) demonstrate a potential mechanism by which the heparan sulfate proteoglycan Dally-like (Dlp) promotes Wg travel, whereas matrix Mmp2 (Metalloproteinase 2) impedes it by inactivating Dlp.